Intensity and patterns redistributive effect of internal migration in Cuba and the Dominican Republic. According DAM and DAME. 2000 and 2010 census rounds - Arelis Rosalén Mora Pérez; José María Suriel Rodríguez; Wiliam Hernández Mondejar (Novedades en Población, 2016)
Aware of the differences and similarities in the socioeconomic and demographic contexts that characterize Cuba and the Dominican Republic, is made from the information collected in the Census of Population and Housing of the two countries in the rounds 2000 and 2010, a study on migration internal. A summary of the management of census questions regarding the recruitment of absolute internal migration of lifetime and recent migration fixed date five years ago. The research is conducted in order to identify how has been the evolution of the intensity, the redistributive effect and profile of internal migration in Cuba and the Dominican Republic as Administrative Divisions Major and Minor (DAM and DAME). Different migration indicators: net migration, proportion of non-migrants, net migration rate (TMN), overall intensity (rate of internal mobility), immigration effectiveness index (IEM), and aggregate net migration rate (TAMN) are used to explain behavior. Migrant profile analysis are performed by age, sex and educational level and regularities are articulated in the redistributive and intensity of internal migration effect generating attractive specialization of these administrative units. Generally, it can be seen in Cuba, the migration intensity between the two census moments remained constant level DAM, while among DAME a decrease of this intensity is appreciated. In the case of the Dominican Republica, reduction stands.